2005
DOI: 10.1111/j.1399-0004.2005.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hereditary non-polyposis colorectal cancer among Uruguayan patients with colorectal cancer

Abstract: Few studies have investigated the frequency of hereditary non-polyposis colorectal cancer (HNPCC) in patients with colorectal cancer (CRC), and these have shown marked geographic variations. The aim of this study was to estimate the frequency of HNPCC in a cohort of Uruguayan CRC patients. We included all patients operated consecutively for CRC in the Hospital Central de las Fuerzas Armadas (Uruguay) between 1987 and 2003. Cases were classified into three groups: (i) those fulfilling Amsterdam criteria; (ii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…The proportion of identified mutations (45.4 percent) is similar to that reported by Rossi et al 8 from Brazil but higher than that reported by Sarroca et al 12 from Uruguay (2/12, 16.6 percent), who speculate that a different genetic profile may exist in the Uruguayan population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion of identified mutations (45.4 percent) is similar to that reported by Rossi et al 8 from Brazil but higher than that reported by Sarroca et al 12 from Uruguay (2/12, 16.6 percent), who speculate that a different genetic profile may exist in the Uruguayan population.…”
Section: Discussionsupporting
confidence: 83%
“…Although molecular and epidemiologic data from North America, Europe, and Asia are widely available in the literature, 7 limited data are available from South America. [8][9][10][11][12] Furthermore, no data on CRC from an Argentine register are available in the MEDLINE index literature.…”
mentioning
confidence: 99%
“…In a review published by Dominguez-Valentín et al, the LS mutation spectrum in South American countries was described [62]. Pathogenic mutations in the MMR genes were identified in patients from Brazil [53], Argentina [63], Uruguay [64], and Colombia [65] (Table 3). Furthermore, the InSIGHT database contains additional information on MMR mutations in additional Hispanic subpopulations, Portugal, and Spain [53].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant risk factors for CRC is family history [2, 3]. Lynch syndrome, often called hereditary non-polyposis CRC (HNPCC), is the most common hereditary colon cancer syndrome and is responsible for approximately 1-3% of cases of CRCs [4][5][6][7][8][9][10][11][12][13][14]. However, in Newfoundland up to 47% of CRC patients come from high-risk and intermediate-risk families [15].…”
Section: Introductionmentioning
confidence: 99%